A new elegant species of Corynandra (Cleomaceae) from Konkan region of Maharashtra, India - Chandore, Arun Nivrutti; Yadav, Usha Shrirang; Yadav, Shrirang Ramchandra (Phytotaxa, 2016)
A new elegant species of Corynandra Schrad. ex Spreng. (Cleomaceae) is described and illustrated from Konkan region of Maharashtra, India. The new species differs from Corynandra chelidonii (L. f.) Cochrane & Iltis by its perennial habit, presence of root suckers, 3–5 foliate basal leaves, flower 5–9 cm across, petals up to 4.5 cm long, stamens up to 250, capsule beak 8–14 mm long, seed testa with blunt tubercles and open, deep cleft.